2024
DOI: 10.1145/3597023
|View full text |Cite
|
Sign up to set email alerts
|

Distributed Task Offloading and Resource Purchasing in NOMA-Enabled Mobile Edge Computing: Hierarchical Game Theoretical Approaches

Abstract: As the computing resources and the battery capacity of mobile devices are usually limited, it is a feasible solution to offload the computation-intensive tasks generated by mobile devices to edge servers in mobile edge computing (MEC). In this paper, we study the multi-user multi-server task offloading problem in mobile edge computing systems, where all the users compete for the limited communication resources and computing resources. We formulate the offloading problem with the goal of minimizing the cost of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Additionally, we explored the potential of COIN to address the computing and memory limitations faced by MEC [2,54]. Moreover, existing studies have demonstrated the effectiveness of OPG solutions for task offloading [51], but they often focus on MEC without considering the BC scalability issues [15][16][17][18][19][20]. Our work bridges this gap by addressing BC data processing tasks and BC mining problems through partial offloading in COIN.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Additionally, we explored the potential of COIN to address the computing and memory limitations faced by MEC [2,54]. Moreover, existing studies have demonstrated the effectiveness of OPG solutions for task offloading [51], but they often focus on MEC without considering the BC scalability issues [15][16][17][18][19][20]. Our work bridges this gap by addressing BC data processing tasks and BC mining problems through partial offloading in COIN.…”
Section: Discussionmentioning
confidence: 99%
“…• The OPG method considers a scenario where OPG offloading via the BC is based on full redundancy. The OPG has generally performed remarkably in solving taskoffloading problems [50][51][52][53] and we included it as a benchmark to compare against our proposed redundancyaware offloading approach.…”
Section: Numerical Simulationsmentioning
confidence: 99%
See 1 more Smart Citation
“…In traffic management, the traffic flow and average speed of a specific section at a specific time are two very important traffic characteristics that describe the traffic conditions of the section [18]. Effective analysis of these two traffic characteristics can accurately study and judge road traffic conditions [19]. Then take corresponding traffic management actions, such as adjusting the time of traffic lights, setting variable lanes, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Using cloud computing technology, we can leverage cloud resources to facilitate distributed training and federated learning [11][12][13]. This approach entails training a global model on a central cloud server, without collecting private data on edge device.…”
Section: Introductionmentioning
confidence: 99%